Pemungutan Kalsium Oksida (CaO) sebagai Adsorben dari Berbagai Jenis Cangkang dengan Proses Kalsinasi - Adifa Azzajalla Robitu; Cut Difasya Auriely Tamami; Mutasim Billah (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Calcium oxide (CaO) is the result of the combustion of calcium carbonate (CaCO3) through a calcination process. It can be utilized as an adsorbent. CaO has been demonstrated to be an effective adsorbent in a variety of applications, particularly in the domains of purification and waste treatment. The presence of calcium carbonate has been observed in various types of shells, including those of eggs and shellfish. The objective of this study is to analyze the calcium oxide produced in the shells of duck eggs, quail eggs, green mussels, rice paddy snails, and kupang. The study will employ XRF analysis to determine the shells that produce the highest calcium oxide. The present study employed a combustion time variation ranging from 24 to 120 minutes at an elevated temperature of 800°C. The results demonstrated that duck eggshells calcined for 120 minutes exhibited the highest calcium oxide content. Subsequent analysis using scanning electron microscopy (SEM) and UV-Vis spectrophotometry was conducted to ascertain the morphology and adsorption power. Consequently, the processing of shell waste has the dual benefits of reducing environmental impact and generating higher economic value through its utilization as an adsorbent.